7 - The Economic Situation in Contemporary Africa: Comment on Questions Posed by Lansana Keita - Bond, Patrick; Dembele, Demba Moussa (Africa Development, 2021)
The economic situation in contemporary Africa is highly problematic, creating populations that are in general much discontented with matters as they now stand. Africa’s populations are now assailed by negative phenomena such as high unemployment; low wages in an environment of high prices (Third World wages and First World prices); low capital accumulation; banks that cater to expatriates of the wealthy mainly; human capital flight; political instability; questionable democracy; weak and inefficient infrastructures, all now supervised by the IMF and the World Bank.